Training in values and the practice of primary health care with oral health students - Fiuza Sanchez, Heriberto; De Paula Silva, Carlos José; Drumond, Marisa Maia; Ferreira e Ferreira, Efigênia (Acta Bioethica, 2012)
The interventions that public health Brazilian system propose, denominated Unique Health System (UHS) depend on the value given to Primary Health Care (PHC). Therefore, human resources involved must be prepared. The aim of this study was to evaluate dimension concepts related to PHC by students of eight and nine periods of Dentistry Department of a Brazilian Public University, with the participation of a sample of students. In order to study the dimensions, one researcher applied individual questionnaires. The answers were analyzed with BioStat 4.0 program. Respondents understand broadly “the process health-disease” and that “adequate technologies” are limited to hard and medium technologies, with little mention to the use of soft technologies. With respect to “humanizing health care”, they belief that ethics represent a compromise with human dignity and that solidarity must be understood politically; furthermore, they establish a link between technical experience and responsibility, reflected in giving priority to the person. On the other hand, they do not understand that it is possible a deep study of ethics and solidarity, understanding them more as “values” which cannot be systematized in curricular content.